DETECTION OF CURRENT CIRCUITS FAULT FOR DIFFERENTIAL CURRENT PROTECTION - M. S. Loman; V. S. Kachenya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2018)
False operation of the differential current protection leads to tripping of the most important electrical power objects. Fault of current transformer’s secondary circuits is one of the most often cause of false operation of the differential current protection. Early determination of this malfunction increases the reliability of the differential current protection and reduces the number of false trips. In the present article the methods of secondary open circuit determining for the differential protection are described. Some of the methods react instantly to the malfunction of secondary current circuits, and the other part identifies fault after a certain time delay. Each of considered methods has its advantages and disadvantages. A new method for determination secondary open current circuits based on the analysis of increments of the RMS values of differential and braking currents has been proposed. In this case, increments are calculated for half the period of the industrial frequency, which provides quick fault determining. The use of the sum and the difference between the increments of the brake and differential currents makes it possible to determine the open circuits in the most sensitive way. The method can be adapted to work with any type of differential protection, including transformer protection. The evaluation of the increment of the RMS current value is performed taking into account the transient process in the Fourier filter. With the aid of a computational experiment, the error limit of such an estimate is determined. The block diagram of algorithm of determination of open circuits on the basis of the analysis of increments of the acting values of brake and differential currents is presented; the principle of its functioning is described. The parameters of operation are determined. The limits of sensitivity of the method are determined, too. The time characteristics of the algorithm have been determined by the method of computational experiment with the of the MatLab Simulink simulation environment.